The Effectiveness of Ulama's Preaching in Changing, Abdullah bin Bayyah's perspective - Sari Nopalisa Putri (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2023)
The Method of Prophetic Preaching according to Abdullah bin Bayyah discusses the highly effective and relevant preaching methods of Prophet Muhammad SAW that are still applicable today. The readers can learn about the principles of effective preaching and how to apply them in daily life. The absence of a clear strategy in implementing preaching activities is also noted. Many preachers lack a clear strategy in carrying out preaching activities, resulting in ineffective preaching that fails to motivate people to increase their religious awareness and social responsibility. This study uses a literature review method, where the researcher collects and reads information from various available sources, then analyzes and evaluates the data obtained. It can be concluded that Sheikh Abdullah bin Bayyah emphasizes the importance of bringing Muslims and non-Muslims closer together, promoting dialogue and tolerance, and avoiding extremism and violence. In addition, scholars have an important role in spreading religious teachings and motivating the people to do good deeds, as well as helping to improve the social and political conditions of a country. The effectiveness of scholars' preaching can be seen from various factors such as their ability to understand and introduce religious teachings well to the community, their success in inspiring and motivating people to worship and improve themselves, as well as the positive influence produced by their preaching on the social and moral life of the community.